2008
DOI: 10.1016/j.antiviral.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscularly administered neuraminidase inhibitor peramivir is effective against lethal H5N1 influenza virus in mice

Abstract: The replication efficiency and multi-organ dissemination of some influenza A (H5N1) viruses requires a rapid (re)evaluation of the available antiviral strategies. We assessed five regimens of the neuraminidase (NA) inhibitor peramivir in mice inoculated with H5N1 virus. The regimens differed by: (1) frequency of administration on first day (once vs twice); (2) duration of administration (1 day vs 8 days); (3) route of administration (intramuscular [IM] injection alone or followed by oral administration). In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 48 publications
(52 reference statements)
0
28
0
Order By: Relevance
“…Peramivir exhibits strong neuraminidase inhibitory activity against influenza A and B viruses [17], including pandemic H1N1 2009 and highly pathogenic viruses, such as the H5N1 subtype [18,19]. The most important characteristics of peramivir are the certainty of drug delivery because it is administered intravenously and its long-lasting antiviral activity.…”
Section: Peramivirmentioning
confidence: 99%
“…Peramivir exhibits strong neuraminidase inhibitory activity against influenza A and B viruses [17], including pandemic H1N1 2009 and highly pathogenic viruses, such as the H5N1 subtype [18,19]. The most important characteristics of peramivir are the certainty of drug delivery because it is administered intravenously and its long-lasting antiviral activity.…”
Section: Peramivirmentioning
confidence: 99%
“…Peramivir, generated by using the structure-based drug design, has three chemical groups that interact with active-site residues of the influenza virus neuraminidase protein, resulting in the tight binding and a slow rate of dissociation [4,5]. Therefore, peramivir offers the advantage of a markedly longer half-life of binding to the neuraminidase active site, permitting less frequent dosing [6].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies with mice and ferrets showed that repeated intramuscular injections of peramivir were effective against infection with HPAIV A/Vietnam/ 1203/04 (H5N1) (7,23). Although mouse and ferret models have provided insight into the pathogenesis of H5N1 HPAIV in mammalian hosts, the pathogenicity in those models cannot be directly extrapolated to humans.…”
mentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that H5N1 HPAIVs were sensitive to NA inhibitors, including oseltamivir, zanamivir, laninamivir, and peramivir (7)(8)(9). Of these, oseltamivir has been the most widely used and was demonstrated to improve the survival of patients, although oseltamivir-resistant H5N1 HPAIVs with mutations at positions H275Y and N295S (N1 numbering) of the NA were isolated from patients during antiviral treatment (10).…”
mentioning
confidence: 99%